2010
DOI: 10.1016/j.acuro.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Efecto en el sangrado perioperatorio durante la resección transuretral de la próstata tras un mes de tratamiento con dutasteride

Abstract: Dutasteride did not significantly impact the studied variables in these non randomized and small sample size settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Hahn et al showed no significant reductions in postoperative bleeding among patients taking 5-alpha-reductase for 2 weeks before transurethral resection of the prostate [21]. In a similar study, Arratia-Maqueo et al also showed no significant reductions in postoperative bleeding among patients taking the same medicine for a longer time period of 4 weeks [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Hahn et al showed no significant reductions in postoperative bleeding among patients taking 5-alpha-reductase for 2 weeks before transurethral resection of the prostate [21]. In a similar study, Arratia-Maqueo et al also showed no significant reductions in postoperative bleeding among patients taking the same medicine for a longer time period of 4 weeks [22]. …”
Section: Discussionmentioning
confidence: 99%
“…In two recent studies, one RCT and an other an observational prospective study, aimed at exploring the role dutasteride versus placebo on reducing blood loss during and after TURP procedures, found no significance in dutasteride's use to reduce blood loss [17, 18]. Hahn et al reported that dutasteride reduced 86–89% of the serum DHT level after 2 weeks of treatment [18].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, there was no significant difference in blood loss between the groups either during or after TURP ( P > 0.05), in addition to no difference in the MVD between the dutasteride group and the control group ( P > 0.05) [18]. In a study by Arratia-Maqueo et al using dutasteride and placebo, they report no difference in blood loss after TURP ( P = 0.88), Hb decrease ( P = 0.73), or resected prostatic chipping weight ( P = 0.87) [17]. However, they do mention that 33% of the patients on dutasteride had significant symptom improvement and did not require TURP [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation